The role of mass media in disease outbreak reporting in the United Republic of Tanzania - Mboera, LEG; Rumisha, SF (Tanzania Journal of Health Research, 2008)
Emerging infectious diseases and the growth of information communication technology have produced new demands and possibilities for disease outbreak information and reporting. An analysis of disease outbreak information and reporting by the Tanzanian mass media was carried out to cover a 12-month period between July 2002 and June 2003. Outbreak episodes reported in four local dailies were collected, compiled and analysed. The disease that received the highest coverage was cholera. Cholera outbreaks were frequently reported from the 3 districts in Dar es Salaam Region. Other epidemic-prone diseases received very little coverage. These included meningitis and rabies. With globalisation and high technological information systems, reports of disease outbreaks are more widely disseminated and more easily accessible than ever before. However, the quality of information is no longer controlled and may be provided out of context, often causing unnecessary public anxiety and confusion. It is important that mass media is provided with accurate epidemiological reports if correct information is to reach the public. The role of media in outbreak reporting is herein discussed in relation to the importance of providing timely and accurate epidemiological information. Tanzania Health Research Bulletin Vol.6(2) 2004: 73-77